Narratives of resilience from Indigenous women in North America and Africa - Azubuike, Chibuzor Mirian (Kansas State University, 2024)
The colonialization of Native people in different parts of the world led to grave consequences for the colonized people. Scholars have examined the various kinds of colonialism and their negative impacts on the Native people who suffered alienation from their lands, cultures, and ancestries. The findings of numerous studies reveal that many treaties signed between Indigenous nations and Europeans were disregarded at the onset of colonialism in full swing in North America and Africa. Colonialism exacerbated this issue by imposing arbitrary boundaries in various African and American societies, resulting in the loss of lands for several tribal nations and the displacement of Indigenous groups from their ancestral lands. Both Native American nations and African societies experienced the adverse effects of colonialism, enduring significant consequences such as land loss and forced displacement and the disruption of the hitherto existing leadership of the Indigenous peoples before their contact with the Europeans and subsequent colonization. The leadership structures that emerged in many colonized societies of Africa and America were in line with the colonizers’ leadership styles. These styles of leadership, as explained by many scholars, led to the emergence of social injustice movements as regards land acquisition, forceful eviction, and, in some cases, brutal treatment of the people. Such treatments include the report from the Uban Indian Health Institute, which shows that the Indigenous women of some tribal nations in the USA and Canada were murdered on their Native lands by non-Native people. Gbenenye (2016) cited the arbitrary creation of boundaries, which led to civil wars and the displacement of Indigenous people from their ancestral lands, like the Bakassi people in Africa, as an aftermath of colonialism and such injustices gave rise to movements such as Missing and Murdered Indigenous Women in the USA and Canada. However, not much has been done on the narratives of resilience among the Indigenous women of North America and Africa. This is the gap that this research sought to fill. This study utilized qualitative research methods, mainly narrative inquiry, with Indigenous women in North America and Africa to elicit data on their intersectional realities. Leadership as practice, complex adaptive system, nego-feminism/Indigenous feminism, and muted group theory constitute the theoretical framework employed in this study. This work situates resilience in the Leadership as Practice framework. As such, I argue that community resilience is a leadership practice. Resilience for Indigenous people is beyond being a trait, it is a commitment to uphold the legacies and sacrifices of their ancestors. The findings of my research show that Indigenous women practice resilience in their everyday lives. Findings from this research further show that there are factors responsible for resilience-building among Indigenous women. These factors include mentorship to acquire skills necessary for them to build resilience in their societies. Finally, the findings of my research show that resilience building is essential for Indigenous women in North America and Africa. Findings from this research would be useful in preventing violence in the event of displacement, as well as in socially integrating people who have suffered forced removal. I recommended some actions that can elevate the voices of Indigenous women in this study, contribute to the discourse on resilience and women’s leadership, and uphold the Indigenous knowledge systems while demonstrating the agency of Indigenous women in North America and Africa.
Keywords: Indigenous; Women; Leadership; Africa; North America; Bakassi